수직고경이 붕괴된 골격성 III급 부정교합자의 악교정 수술 치험례 - 최윤경(Youn-Kyung Choi); 김용덕(Yong-Deok Kim); 박수병(Soo-Byung Park); 김용일(Yong-Il Kim); 김성식(Seong-Sik Kim); 손우성(Woo-Sung Son) (Journal of dental rehabilitation and applied science, 2016)
Patients who lost posterior teeth due to periodontitis or dental caries have collapsed vertical dimension, unstable occlusion and change of the mandibular position. In particular, patients in orthognathic surgery, clinician should re-establish the pre-operative stable position of mandibular condyle in articular fossa and favorable vertical dimension for high post-operative stability of mandible. Therefore, interdisciplinary approach and co-operation, including prosthetics, orthodontics, oral and maxillofacial surgeon, from diagnosis and treatment plan is important to get a good outcome. This case report was patients who had collapsed occlusal plane due to severe dental caries on maxillary molars with skeletal Class III malocclusion. Before orthognathic surgery, resetting of maxillary occlusal plane with temporary removable denture was performed. Then successful multidisciplinary approach was done and lead to acceptable clinical outcome. 치주 질환이나 치아 우식으로 인해 구치부 치아가 상실된 환자들은 대합치 정출 및 인접치 경사가 발생하여, 교합평면의 붕괴나 수직 고경의 상실로 하악골 위치 변화가 나타날 수 있다. 특히 악교정 수술 환자에서, 이런 증상이 나타날 경우 하악과두가 관절와 내에서 안정화된 위치에 존재하여 술 후 안정성을 높일 수 있도록, 술 전 수직 고경을 재설정하는 치료가 필요하다. 따라서 보철, 교정, 구강악안면외과 등 다분야에서 진단 및 치료 계획에서부터 원활한 의사소통을 통한 양호한 치료 결과를 얻을 수 있도록 협력하는 것이 중요하다.